Management of Personnel Information System Application (Simpeg) in North Minahasa Regency - Asiking, Ulfa Suryana; Pangkey, Itje; Mamonto, Fitri H. (JR Education, 2025)
This study aims to analyze the management of the Personnel Information System (SIMPEG) application in North Minahasa Regency, focusing on three main aspects: human resource (HR) management, facilities and infrastructure, and budget support. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study indicate that although SIMPEG has been implemented quite well, there are several significant obstacles. First, from the HR side, there was a competency gap in operating the SIMPEG advanced module, as well as resistance from employees who still rely on manual systems. Second, facilities and infrastructure, such as network infrastructure and hardware, that are starting to become obsolete hamper system performance. Third, less flexible budget support causes delays in infrastructure rejuvenation and HR training. Based on these findings, this study recommends increasing HR capacity through continuous training and certification, improving IT infrastructure, and optimizing budget allocation to support system sustainability. With these steps, it is hoped that SIMPEG can function more effectively in supporting transparent and efficient personnel governance in North Minahasa Regency.